Zařízení na sváření filamentu pro 3D tisk - Roden, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Tato bakalářská práce se zabývá svářením filamentů do 3D tiskáren. Při tisku často zbývá část filamentu, pro kterou už není využití díky její malé délce. V této práci je řešena konstrukce zařízení ke spojování těchto zbytků struny, popřípadě i delších kusů. V první části je vytvořena rešerše zabývající se typy 3D tiskáren, materiálem tiskových strun a problematice procesu svaření. Ve druhé části je využito načerpaných poznatků k vytvoření vlastního návrhu zařízení. Zahrnuje rozbor použitelnosti jednotlivých materiálů a návrhů konstrukce. V poslední části je řešeno konkrétní konstrukční řešení jednotlivých komponent.

This bachelor’s thesis deals with filament welding in 3D printers. During the print, there is often an extra part of the filament, that can be no longer used due to its small length. In this thesis I deal with the equipment construction for connecting these remnants of the cord or even longer pieces. In the first part is a search which deals with types of 3D printers, material of filaments and the issue of the welding process. In the second part, the acquired knowledge is used to create your own device design. More precisely, the analysis of the usability of individual materials and construction designs. In the last part I deal with a specific form solution of individual components.
A device for welding 3D printing filament
Keywords: sváření; filament; 3D tisk; welding; filament; 3D printing